Synthesis of electrophilic N-heterocyclic carbenes based on azahelicene. Issue 30 (23rd July 2020) - Morgante, Pierpaolo; Captain, Burjor; Chouinard, Christopher D.; Peverati, Roberto; Takenaka, Norito
Graphical abstract: Highlights: Helical-chiral imidazopyridine-2-yilidenes were synthesized from 2-aza[6]helicene. Energies of their frontier orbitals were analyzed by the density functional theory. Helicene annelation lowered the energy of π-acceptor orbital by 1.47 eV. Abstract: Helical-chiral analogues of imidazopyridine-2-yilidene were synthesized from 2-aza[6]helicene. The energies of their frontier orbitals were analyzed by the density functional theory calculations. The exceedingly large extension of NHC's π system by helicene annelation significantly enhanced the π electron-accepting properties of the carbene center while the strong σ electron-donating properties of imidazopyridine-2-yilidenes were retained.